Endovascular treatment of cerebral aneurysms: a retrospective study of 163 embolized aneurysms Tratamento endovascular de aneurismas cerebrais: estudo de 163 aneurismas embolizados - João Renato Figueiredo Souza; Marcelo Otoch; Sérgio Pouchain Ribeiro; Francisco Ramos Júnior; João Paulo Cavalcante de Almeida; Lucas Alverne Freitas de Albuquerque; Moysés Loiola Ponte de Souza (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To present the results of cerebral aneurysms treated by endovascular technique. METHOD: Retrospective analysis of patient files of Hospital Geral de Fortaleza, Brazil. RESULTS: We report the results of 163 cerebral aneurysms treated by endovascular techniques from January 2002 to October 2005. Patients with ruptured aneurysms (87.2%), according to Hunt-Hess scale were: 33.7% HH I, 28.4% HH II, 24.1% HH III, 13.8% HH IV. The Fisher scale grade IV was the most common (39.7%). Remodeling, coil embolization, arterial occlusion and histoacryl embolization were the techniques employed. Effective occlusion was achieved in 87.7%, partial occlusion in 5.3% and non-effective occlusion in 7.0% of the patients. Glasgow outcome scale results were: 76.3% GOS 5, 5.0% GOS 4, 5.8% GOS 3, 1.4% GOS 2 and 11.5% GOS 1. CONCLUSION: Endovascular treatment seems to be feasible within Brazilian public health system, with results as good as those obtained in larger international centers. OBJETIVO: Apresentar os resultados de aneurismas tratados pela técnica endovascular. MÉTODO: Análise retrospectiva de prontuários do Hospital Geral de Fortaleza, Brasil. RESULTADOS: Apresentamos os resultados de 163 aneurismas cerebrais tratados por técnicas endovasculares de Janeiro de 2002 a Outubro de 2005. Os pacientes com aneurismas rotos (87,2%) eram, segundo a escala de Hunt-Hess: 33,7% HH1; 28.4% HH II, 24.1% HH III, 13.8% HH IV. O Grau IV da escala de Fisher foi o mais comum (39,7%). Empregaram-se as técnicas de remodeling, espiras metálicas, oclusão arterial e embolização com histoacryl. Foi obtida oclusão efetiva em 87,7%, oclusão parcial em 5,3% e oclusão não-efetiva em 7,0% dos casos. De acordo com a Glasgow outcome scale, os resultados foram: 76,3% GOS 5, 5,0% GOS 4, 5,8% GOS 3, 1,4% GOS 2 e 11,5% GOS 1. CONCLUSÃO: A aplicação de técnica endovasculares mostra-se viável na rede pública brasileira, com resultados comparáveis aos de grandes centros mundiais.